The interconnected work of a preschool educational organization with a family, mahalla in order to develop children in order to prepare them for school - Buranova Shohnoza Abdurazakovna (Genius Journals, 2023)
This article is devoted to the relationship between the work of a preschool educational organization, family and mahalla in order to enroll children in a preschool educational organization to prepare them for school. About the variety of forms of work with parents of preschool children.
Keywords: Professional activity of an educator; vocation; goals of family education